2010
DOI: 10.1111/j.1540-8167.2010.01728.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Anatomy for the Electrophysiologist: Ablation for Atrial Fibrillation. Part I: Pulmonary Vein Ostia, Superior Vena Cava, Vein of Marshall

Abstract: Ablation procedures for atrial fibrillation (AF) have become an established and increasingly used option for managing patients with symptomatic arrhythmia. The anatomic structures relevant to the pathogenesis of AF and ablation procedures are varied and include the pulmonary veins (PVs), other thoracic veins, the left atrial myocardium, and autonomic ganglia. Exact regional anatomic knowledge of these structures is essential to allow correlation with fluoroscopy and electrograms, and, importantly, to avoid com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 63 publications
0
28
0
Order By: Relevance
“…17, 18 Similar to extensions of left atrial muscle into PV, right atrial muscle extends into SVC. 5, 6 Chen et al 18 previously described in canine SVC cardiomyocytes, the presence of spontaneously beating APs displaying phase 4 depolarization. The results of our study demonstrate a marked diversity of action potential characteristics in the canine SVC sleeve, including action potentials with short and long durations, with and without phase 4 depolarization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17, 18 Similar to extensions of left atrial muscle into PV, right atrial muscle extends into SVC. 5, 6 Chen et al 18 previously described in canine SVC cardiomyocytes, the presence of spontaneously beating APs displaying phase 4 depolarization. The results of our study demonstrate a marked diversity of action potential characteristics in the canine SVC sleeve, including action potentials with short and long durations, with and without phase 4 depolarization.…”
Section: Discussionmentioning
confidence: 99%
“…68 Like in PV sleeves, atrial myocardial tissue has been demonstrated to extend into the SVC sleeves for approximately 2–5 cm. 5, 6 Extrasystolic activity arising from non-PV atrial structures, such as SVC, may compromise the success of PV isolation for the treatment of AF. 7 In addition to PV isolation, SVC isolation improves the outcome of AF ablation in patients with paroxysmal AF.…”
Section: Introductionmentioning
confidence: 99%
“…16 -21 Additionally, the role of venous structures, such as the coronary sinus and the Marshall bundle and vein, during AF RF ablation has been studied extensively. [25][26][27][28] The present work was not designed to evaluate the effects of RF near atrial arteries and limits itself to describing their presence at AF ablation sites. Nonetheless, on the basis of the existing data, it is plausible to suppose that interactions likely occur between the RF application on the endocardial surface and the subjacent artery on the subepicardial surface because of the relatively small thickness of the atrial wall.…”
Section: Discussionmentioning
confidence: 99%
“…The specific risks of AF ablation reflect potentially extensive ablation as well as the proximity of atria to adnexae such as the esophagus, phrenic nerves and other vasculature 105, 106 . Awareness of these risks has improved procedural technique, e.g.…”
Section: Complications Of Af Ablationmentioning
confidence: 99%